Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1097/wnr.0000000000000829
|View full text |Cite
|
Sign up to set email alerts
|

Memory-related functional connectivity in visual processing regions varies by prior emotional context

Abstract: Memory retrieval involves the reactivation of processes that were engaged at encoding. Using a Generalized Linear Model to test for effects of valence, our prior study (Bowen & Kensinger, in press) suggests memory for information previously encoded in a negative context reengages sensory processing regions at retrieval to a greater extent than positive. Here, we used partial least squares analyses of the same dataset to determine whether this valence-specific processing was one of the dominant patterns in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In previous fMRI work, including a study using the same paradigm employed in the present study, our lab has shown that neural recapitulation is greater for negatively valenced stimuli than neutral or positive (Bowen & Kensinger, 2017a, 2017b. Only a few studies have examined how emotional content from encoding affects the ERP response at retrieval (Jaeger et al, 2009;Maratos & Rugg, 2001;Smith, Henson, Dolan, & Rugg, 2004).…”
Section: Early Effects Of Emotional Encoding Context At Retrievalmentioning
confidence: 80%
See 2 more Smart Citations
“…In previous fMRI work, including a study using the same paradigm employed in the present study, our lab has shown that neural recapitulation is greater for negatively valenced stimuli than neutral or positive (Bowen & Kensinger, 2017a, 2017b. Only a few studies have examined how emotional content from encoding affects the ERP response at retrieval (Jaeger et al, 2009;Maratos & Rugg, 2001;Smith, Henson, Dolan, & Rugg, 2004).…”
Section: Early Effects Of Emotional Encoding Context At Retrievalmentioning
confidence: 80%
“…In the current work, we employed a paradigm known to elicit greater recapitulation for negative versus positive contexts in fMRI (Bowen & Kensinger, 2017a, 2017b. Neutral words were paired with an unrelated neutral, positive, or negative picture during memory encoding.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, our prior fMRI work has shown that neutral retrieval cues can reactivate some of the emotion-related properties associated with the prior encoding experience. Successful memory for neutral words (Bowen & Kensinger, 2017a, 2017b and line drawings (Kark & Kensinger, 2015 is associated with greater recapitulation in regions including those within the ventral visual stream to a greater extent for items previously encoded in a negative compared with a neutral or positive context. This is true although the emotional content is no longer present at the time of retrieval (for a review, see Bowen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A finding with important practical and theoretical implications is that negatively, as compared to positively, valenced pictures and scenes are associated with superior recognition and sense of recollection (Ochsner, 2000), particularly with respect to their central visual details (Christianson & Loftus, 1991; Kensinger, 2009; Kensinger, Garoff-Eaton, & Schacter, 2006). Some reasons for this may be that negatively valenced scenes recruit more sensory processing areas at encoding (Kensinger & Schacter, 2008; Mickley & Kensinger, 2008) and that there is a greater recapitulation of this processing at retrieval (Bowen & Kensinger, 2017). Much less is known about the phenomenological processes operating at retrieval that correspond to or could mediate neural differences in the processing of positive and negative scenes.…”
mentioning
confidence: 99%